Strategi Kemitraan melalui Program Sistem Integritas Lokal sebagi Upaya Pemberantasan Korupsi Tahun 2017 - Muhammad Aliya Zaky Haidar; Teguh Yuwono (Journal of Politic and Government Studies, 2018)
Corruption is a problem for Semarang City administration. This research is motivated by weak leadership in efforts to eradicate corruption; weak commitment in efforts to eradicate corruption; and a bad work culture that provides opportunities and discretion in all forms of irregularities that lead to corruption. This study aims to determine the efforts in eradicating and preventing corruption through a partnership strategy between the Semarang City Government and TII and PATTIRO Semarang regarding the Implementation of Local Integrity Systems. Using the theory of Good Governance, Partnership, commitment of local governments, anti-corruption policies.This type of research is descriptive analytic through a qualitative approach. Data sources in this study were obtained from interviews with resource persons and archives or documents relating to research. The sampling technique uses purposive sampling. Data collection techniques used in this study are interviews, observations, and documents. This type of research is explanatory analytical through a qualitative approach.The results of this study indicate that the partnership strategy between the Semarang City Government and TII and PATTIRO Semarang in forming a systemic government institution with integrity to eradicate corruption in the Semarang City Government was quite successful. This can be known based on the results of this study which shows that there are several actions in the program that have been identified and dictated by TII and PATTIRO Semarang. Furthermore, the implementation has also obtained results, one of which is the decline in the receipt of gratification from the Semarang city government to the increase in development investment in Semarang City. According to the above conclusions can produce suggestions that in an organization of cooperation or partnership have the duties and roles of each of the perpetrators, should the efforts to prevent and eradicate corruption is carried out an increase in the roles and / or duties of the perpetrators so that the implementation can be more effective results use as efficiently as possible the use of resources.Keywords: Corruption, partnership, Good Governance, Commitment.